Stepwise synthesis, characterization, DNA binding properties and cytotoxicity of diruthenium oligopyridine compounds conjugated with peptides. Issue 10 (13th February 2018) - Ypsilantis, Konstantinos; Plakatouras, John C.; Manos, Manolis J.; Kourtellaris, Andreas; Markopoulos, Georgios; Kolettas, Evangelos; Garoufis, Achilleas
Abstract : The conjugation of peptides to diruthenium complexes was achieved. Abstract : Although the interactions of oligopyridine ruthenium complexes with DNA have been widely studied, the biological activity of similar diruthenium oligopyridine complexes conjugated with peptides has not been investigated. Herein, we report the stepwise synthesis and characterization of diruthenium complexes with the general formula [(L a )Ru(tppz)Ru(L b )] n + (tppz = 2, 3, 5, 6-tetra(2-pyridyl)pyrazine, L a = 2, 2′:6′, 2′′-terpyridine or 4-phenyl-2, 2′:6′, 2′′-terpyridine and L b = 2, 2′:6′, 2′′-terpyridine-4′-CO(Gly 1 -Gly 2 -Gly 3 -LysCONH2 ) (5 ), (6 ), n = 5; 2, 2′:6′, 2′′-terpyridine-4′-CO(Gly 1 -Gly 2 -Lys 1 -Lys 2 CONH2 ) (7 ), (8 ), n = 6; 2, 2′:6′, 2′′-terpyridine-4′-CO(Ahx-Lys 1 Lys 2 CONH2 ) (9 ), (10 ), n = 5, Ahx = 6-aminohexanoic acid). The compounds [(trpy)Ru(tppz)Ru(trpy-CO2 H)](PF6 )4, (2 )(PF6 )4, [(ptrpy)Ru(tppz)Ru(trpy-CO2 H)](PF6 )4, (3 )(PF6 )4 and [(ptrpy)Ru(tppz)Ru(trpy)](PF6 )4, (4 )(PF6 )4 were also characterized by single crystal X-ray methods. Moreover, the interactions of the chloride salts (5 ), (6 ) and (4 ) with the self-complementary dodecanucleotide duplex d(5′-CGCGAATTCGCG-3′)2 were studied by NMR spectroscopic techniques. The results show that complex (4 ) binds in the central part of the oligonucleotide, from the minor groove through the ligand ptrpy, while the ligand trpy, which was located on the other side of the diruthenium core, does not contribute to the binding. Complex (5 ) binds similarly, through the ligand ptrpy. However, the induced upfield shifts of the ptrpy proton signals are significantly lower than the corresponding ones in the case of (4 ), indicating much lower binding affinity. This is clear evidence that the tethered peptide Gly 1 -Gly 2 -Gly 3 -Lys 1 CONH2 hinders the complex binding, even though it contains groups that are able to assist it ( e.g., the positively charged amino group of lysine, the peptidic backbone, the terminal amide). Complex (6 ) shows a non-specific binding, interacting through electrostatic forces. The chloride salts of (4 ), (5 ) and (6 ) had insignificant effects on the cell cycle distribution and marginal cytotoxicity (IC50 > 750 μM) against human lung cancer cell lines H1299 and H1437, indicating that their binding to the oligonucleotide is not a sufficient condition for their cytotoxicity.